Need to Belong dan Kualitas Persahabatan - Monica, Namira; Herawati, Icha; Napitupulu, Lisfarika; Nugroho , Sigit (UIR Press, 2021)
Humans are social creatures who need other people in their lives. Among teenagers and adults having a friend or close friend is very supportive of individual survival. Individuals will do their best for their social environment and feel attached, this is because of the need to belong in friendly relationships. The purpose of this study was to see whether there was a significant relationship between Need to belong and the Quality of Friendship. The subjects of this research are the millennial generation and the gadget generation in the city of Pekanbaru, amounting to 300 people. The sampling technique used purposive sampling. The data collection method uses the Need to Belong scale compiled by Leary, et al (2013) which amounted to 10 items and the Friendship Quality scale adapted from Prayona (2017) which amounted to 21 items. Data analysis using Spearman correlation where the results show a significant correlation coefficient with a value of 0.353 (p < 0.01). From these results, it can be concluded that there is a relationship between need to belong and the quality of friendship.